Estudio de mercado para conocer el interés de la demanda nacional sobre turismo rural en el cantón Chone - Moreira Basurto, Ginger Estefanía (2022)
The objective of this research was to prepare a market study that would allow distinguishing the interest in rural tourism in Chone, applying a non-experimental exploratory level methodology with a mixed approach, which was developed from analytical, synthetic, descriptive and documentary methods. In the first phase of diagnosis, the characterization matrix, involved, EFE - EFI and SWOT was used to know the territorial and tourist reality. The second phase covered the market study with the application of 384 tourist surveys, analysis of the competitive matrix and review of the offer in the inventory and cadastre. Phase three used the 5W2H model in the action plan. This study found as results, the potential of PTI, but the non-existence of tourism products, due to the lack of accessibility and basic services, evidencing limited cooperation and support between the public-private sectors, on the other hand, the presence of 83 establishments makes up the tourist base and receives clients from Pichincha, Manabí, Guayas and Tungurahua, who are interested in practicing rural activities, however the tourist infrastructure is abundant in the city compared to the rest of the city rural zone. Therefore, the planning was directed towards strategies of the public sphere, quality of services, creation of new products and offers, tourism promotion, innovation, social networks and tourism content, which allows the proper functioning of the tourism system, with the purpose of guarantee a planned territory, where you can live a real rural experience, and not based exclusively on publicity.